Risk factor of pneumonitis on dose-volume relationship for chemoradiotherapy with durvalumab: Multi-institutional research in Japan. (July 2021) - Oshiro, Yoshiko; Mizumoto, Masashi; Sekino, Yuta; Maruo, Kazushi; Ishida, Toshiki; Sumiya, Taisuke; Nakamura, Masatoshi; Ohkawa, Ayako; Takizawa, Daichi; Okumura, Toshiyuki; Tamaki, Yoshio; Sakurai, Hideyuki
Highlights: This is a study focus on radiation dose-volume parameters in use of durvalumab. Dose-volume relation and pneumonitis was retrospectively investigated in 91 patients. Pneumonitis developed in 88% patients at a median of 4.1 months after radiotherapy. ≥Grade 2 and ≥ grade 3 pneumonitis were observed in 34% and 12% of the patients. In use of durvalumab after concurrent chemoradiotherapy, V20 should be < 18.77%. Abstract: Objectives: To estimate appropriate dose-volume parameters for avoidance of pneumonitis in use of chemoradiotherapy and durvalumab for treatment of lung cancer. Materials and methods: Patients with non-small cell lung cancer treated with concurrent chemoradiotherapy followed by durvalumab at 9 centers were enrolled in the study. Three-dimensional radiotherapy, intensity modulated radiotherapy, and proton beam therapy were used. The frequency and severity of pneumonitis and the dose-volume relationship for normal lung were evaluated. Univariable and multivariable analyses were conducted to identify risk factors. A covariate adjusted hazard ratio was then estimated for the percentages of normal lung volume irradiated at ≥ X Gy (Vx) (X = 5–40) and lung volume non-irradiated at ≥ X Gy (X = 5–40), with the covariates selected in the variable selection. Cumulative incidence functions and covariate adjusted hazard ratios were also estimated for dichotomized variables, with estimated cut-off points. Results: A total of 91 patients were enrolled in the study. The median time from the start of radiotherapy to development of pneumonitis was 4.1 months. Pneumonitis was observed in 80 patients (88%), including grade 2 or severe pneumonitis in 31 (34%) and ≥ grade 3 pneumonitis in 11 (12%). Pneumonitis was inside the irradiation field in 73 of the 80 patients (91%). The selected factors for ≥ grade 2 pneumonitis were V20, and primary site (upper lobe) in multivariable analysis. The cut off value of V20 was 18.99%, and there was a significant difference between V20 of < 18.77 and ≥ 18.77. Conclusion: Though there are some limitation of this study, the basic concept of concurrent chemoradiotherapy with an emphasis on V20 remains unchanged in use of durvalumab. However, we recommend reduction of V20 to as small a value as possible in use of this therapy.